Evaluation of diagnostic tools for potassium management in soybean - Charbonnier Bascou, Diego A. (Kansas State University, 2022)
Three studies were conducted to evaluate soil test methods and tissue analysis as diagnostic tools for potassium (K) in soybean (Glycine max). The first study assessed the relationship between K adsorption by cation exchange resins (CER) and K uptake by soybean in field conditions. The study was conducted at two locations with contrasting soil test K levels and two treatments, including a control (0 kg K₂O ha⁻¹) and a high K rate with 168 kg K₂O ha⁻¹ applied pre-plant and incorporated. Cation exchange resins were buried in the field in multiple periods to cover the entire soybean reproductive growth stages. In addition, whole plant samples were collected at R2, R4, and R6 stages to measure plant K uptake. Soil volumetric water content and soil temperature were measured using a TEROS 11 sensor. This study found that CER tends to decrease in inverse proportion to plant K uptake, suggesting a measure of soil K surpluses because of root competition. The fertilized plots were able to maintain higher K supply rates during the peak plant demand. Depending on each location, soil temperature and soil moisture content were highly correlated with CER adsorption in control plots. The second study evaluated tissue nutrient concentration and nutrient ratios as predictors of soybean response to K fertilization. It was conducted at eight locations throughout eastern Kansas during 2019 and 2020. Four treatments were selected to evaluate soybean response to K fertilization. Treatments included a control with no K fertilization and rates with 56 kg K₂O ha⁻¹ increments until reaching a maximum of 168 kg K₂O ha⁻¹. Aboveground plant samples were collected at V4, R2, R4, and R6 stages to measure plant K and Magnesium (Mg) concentration. K concentration and K/Mg ratio at V4 growth stage were well correlated to K uptake at R6 and grain yield. Considering grain yield, the critical concentration range for K and K/Mg ratio was 16.4 to 18.0 g kg⁻¹ and 2.3 to 2.4, respectively. The nutrient ratio was slightly better in predicting K uptake. The third study compared different soil test K (STK) methods and evaluated the correlation to soybean yield and K uptake response in low testing soils. Additionally, the study assessed the effect of sampling moment on STK results for NH₄OAc and Mehlich-3 tests using dry and field moist samples. It was conducted at eight locations throughout eastern Kansas during 2019 and 2020. The treatments were a control with no K fertilization and rates with 56 kg K₂O ha⁻¹ increments until reaching a maximum of 168 kg K₂O ha⁻¹. Aboveground plant samples were collected at R6 stage to measure plant K uptake. In general, moist tests were better correlated to K response than dry tests, especially with NH₄OAc. Among all evaluated methods, the CaCl₂ dry and moist, NH₄OAc moist, Resin K, and NaBPh₄ tests were the best when correlating to relative yield and K uptake. CaCl₂ dry is one the easiest and cheapest tests, also having a consistent correlation coefficient (around 0.70 for both variables). Furthermore, it might be an alternative to the NH₄OAc moist test because of the high correlation (r=0.91). Three out of eight locations had STK changes for dry samples regardless of K fertilization between fall and the subsequent spring sampling. However, when considering moist samples, almost all locations had little or no STK change. Overall, the NH₄OAc moist test was one of the best methods to estimate K availability in low testing soils; however, other non-conventional tests like CaCl₂ dry might perform similarly but without the typic disadvantages of moist samples. Abbreviations: K, potassium; CER, cation exchange resins; Mg, Magnesium; STK, soil test potassium;
Keywords: Potassium; Cation exchange resins; Soybean